Cardiac rehabilitation is associated with lower 1-year all-cause mortality in primary pulmonary hypertension. (11th May 2021) - Kleinnibbelink, G; Buckley, BJR; Harrison, SL; Williams, N; Fazio-Eynullayeya, E; Underhill, P; Van Dijk, APJ; Lip, GYH; Thijssen, DHJ
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Despite introduction of pharmacological therapies to improve outcomes of pulmonary hypertension (PH), poor long-term survival remains present. Cardiac rehabilitation may be an alternative strategy to improve survival. However, no study directly linked CR to mortality in PH patients. Therefore, adopting a retrospective observational study using a large electronic medical record (EMR) database, the objective of this study was to compare mortality between patients with primary PH with CR versus a propensity-matched control group of PH without CR. Methods. The retrospective analysis was conducted on December 14, 2020 using anonymized data within TriNetX, a global federated health research network with access to EMRs from participating academic medical centres, specialty physician practices, and community hospitals, predominantly in the United States. All patients were aged ≥18 years with primary PH recorded in EMRs at least 18-months before the search date to allow for 1-year follow-up from CR. Using logistic regression, patients with PH with an EMR of CR were 1:1 propensity score-matched with PH patients without CR for age, sex, race, diseases of the respiratory system, disease of the circulatory system, hypertensive disease, heart failure, diabetes mellitus, chronic kidney disease, cerebrovascular disease, cardiovascular procedures and cardiovascular medications. Results. In total, 70, 875 patients with primary PH met the inclusion criteria for the control group and 637 patients with primary PH met the inclusion criteria for the CR and exercise cohort (Table 1). Using the propensity score-matched cohort, and excluding patients with outcomes outside the measurement window, mortality at 1-year from CR was proportionally lower with mortality of 13.9% (n = 87 of 628 patients) in the CR and exercise cohort compared to 21.0% (n = 133 of 632 patients) in the controls (OR 0.60, 95% CI 0.45-0.81). Conclusion. In conclusion, the present study of 1, 264 patients with primary PH suggests that CR is associated with 40% lower odds of 1-year mortality, when compared to propensity score-matched patients without CR or exercise programmes.